1790 Oxidative Stress and Clinical Outcome of Preterm Infants Resuscitated with Different Concentrations of Oxygen. (October 2012) - Aversa, S; Marseglia, L; Arco, A; Manfrida, M; Salpietro, C; Barberi, I; Reiter, RJ; Gitto, E
Abstract : Background and Aims: Preterm infants are more sensitive to oxidative stress than older humans. Hyperoxic exposure, although essential for survival of neonates, induces excessive production of reactive oxygen metabolites which could be responsible of morbidities in these babies. Aims of this study were to evaluate the incidence of mortality and bronchodysplasia in preterm infants resuscitated at birth with different concentrations of oxygen. Secondary outcome was to evaluate the serum level of oxdative stress markers in the same population of infants. Methods: A randomized clinical trial has been performed in NICU of University of Messina, Italy. Results: 60 preterm infants (gestational age < 32 weeks) were recruited and randomly divided into three groups (40%, 60% and 100% of fractional inspired oxygen). We didn't find difference in mortality ( p 0, 877), but bronchodysplasia was represented only in the group of 100% oxygen ( p <0.01). These newborns had also a longer time of ventilation ( p 0, 001) and hospitalization ( p 0, 007) and a higher incidence of pneumothorax ( p <0.01). Serum levels of Interleukin-1β and nitrosylated protein were higher in preterm infants resuscitated with 100% oxygen in comparison with the other two groups of infants, which instead presented a significant reduction of interleukin-10 levels. Conclusions: In our study, the exposure of preterm infants to higher oxygen concentrations at birth is correlated with poor respiratory outcome without influencing neonatal mortality. Imbalances between pro- and anti-inflammatory cytokines may therefore be early indicators of developing chronic lung disease.